Cervical cancers diagnosed after negative results on cervical cytology: perspective in the 1980s. Issue 6740 (23rd June 1990) - Mitchell, H; Medley, G; Giles, G
Abstract : OBJECTIVES–To assess the magnitude of the problem of interval cancers of the cervix (those that are diagnosed within a short time after negative screening test results) in the 1980s, to compare the nature of interval cancers in younger women with that in older women, and, by reviewing negative cervical smears, to determine the proportion of interval cancers that might represent the development of malignancy anew compared with the proportion that might be associated with difficulties in sampling or errors in reporting. DESIGN–An audit of the interval cases of cervical cancer that had been diagnosed within 36 months of a smear having been reported as negative by the Victorian Cytology Gynaecological Service among women registered with cervical cancer during 1982-6. SETTING–The Victorian Cytology Gynaecological Service, a free public sector cytology laboratory in Victoria, Australia. SUBJECTS–138 Women, all of whom had had cervical cancer diagnosed during the 36 months after having had a negative cervical smear. Subjects were divided into two age groups: younger women, aged less than 35; older women, aged 35-69. INTERVENTIONS–Negative slides were reviewed for evidence of optimal sampling and for the presence of cellular abnormalities that had been missed at the time of the original reporting. MAIN OUTCOME MEASURES–The number of interval cases of cancer of the cervix registered during 1982-6. The proportion of interval cases occurring in younger women and the proportion occurring in older women. Division of women into three risk categories based on clinical history and screening history that broadly corresponded to the probability that a diagnosis of cervical cancer might be expected during the 36 months after the issuing of a negative smear report. RESULTS–138 Of 1044 (13.2%) women who had been registered with cervical cancer during 1982-6 had had one or more negative smears during the 36 months preceding the diagnosis of cancer. Interval cancers comprised a larger proportion of registrations of cervical cancer in women aged less than 35 years than in women aged 35-69 (21.1% v 11.0%, p less than 0.01). Women with interval cancer who had had at least three negative smears during the 10 years before the diagnosis of cancer were commoner in the younger age group than in the older age group (7.0% v 2.5%, p less than 0.01). When, however, the number of observed cases of squamous cell carcinoma was related to the number of expected cases in the absence of screening, no significant difference was found between the two age groups (6.8% v 4.8%, p greater than 0.10). The rate of diagnosis of interval cancer per 100, 000 negative tests was lower among younger women than among older women (10/100, 000 v 16/100, 000). Review of the negative slides showed that 11.9% were again considered to be negative with an optimal sample having been obtained as evidenced by the presence of endocervical cells or metaplastic cells, or both. CONCLUSIONS–Interval cancers might comprise a larger proportion of all registered cases of cervical cancer among younger women owing to the larger proportion of such cancers being prevented in this age group. Among women with interval cancer review of the negative slides showed that most were accounted for by suboptimal sampling or by errors of reporting.